2022
DOI: 10.3390/ijms23158373
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous ANP Treatment Ameliorates Myocardial Insulin Resistance and Protects against Ischemia–Reperfusion Injury in Diet-Induced Obesity

Abstract: Increasing evidence suggests natriuretic peptides (NPs) coordinate interorgan metabolic crosstalk. We recently reported exogenous ANP treatment ameliorated systemic insulin resistance by inducing adipose tissue browning and attenuating hepatic steatosis in diet-induced obesity (DIO). We herein investigated whether ANP treatment also ameliorates myocardial insulin resistance, leading to cardioprotection during ischemia–reperfusion injury (IRI) in DIO. Mice fed a high-fat diet (HFD) or normal-fat diet for 13 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
2
4
0
Order By: Relevance
“… 17 In addition, we reported that in mice fed a high‐fat diet, the administration of exogenous A‐type natriuretic peptide ameliorated systemic insulin resistance by attenuating hepatic steatosis and inducing adipose tissue browning and furthermore ameliorated myocardial insulin resistance and protected against ischaemia–reperfusion injury. 18 , 19 In the present study, the levels of liver enzymes, such as ALT, ALP, and γ‐GTP, tended to decrease after ARNI treatment. However, the SEM analyses failed to show a significant relationship between the initiation of ARNI treatment and improvement in the liver function due to missing data.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“… 17 In addition, we reported that in mice fed a high‐fat diet, the administration of exogenous A‐type natriuretic peptide ameliorated systemic insulin resistance by attenuating hepatic steatosis and inducing adipose tissue browning and furthermore ameliorated myocardial insulin resistance and protected against ischaemia–reperfusion injury. 18 , 19 In the present study, the levels of liver enzymes, such as ALT, ALP, and γ‐GTP, tended to decrease after ARNI treatment. However, the SEM analyses failed to show a significant relationship between the initiation of ARNI treatment and improvement in the liver function due to missing data.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, we previously reported that natriuretic peptides, which are increased by neprilysin inhibition, could halt the progression to diabetes by improving insulin resistance under the metabolically harmful condition of heart failure 17 . In addition, we reported that in mice fed a high‐fat diet, the administration of exogenous A‐type natriuretic peptide ameliorated systemic insulin resistance by attenuating hepatic steatosis and inducing adipose tissue browning and furthermore ameliorated myocardial insulin resistance and protected against ischaemia–reperfusion injury 18,19 . In the present study, the levels of liver enzymes, such as ALT, ALP, and γ‐GTP, tended to decrease after ARNI treatment.…”
Section: Discussionsupporting
confidence: 51%
“…A continuous subcutaneous infusion of saline was conducted in the DM + saline and DM + NPRC −/− groups, respectively, and infusion of ANP (ANP1-28, MCE, USA; 0.5 μg/kg per minute), BNP (BNP1-32, MCE, USA; 0.03 μg/kg per minute), and CNP (CNP1-22, TargetMol, USA; 0.1 μg/kg per minute) was performed in the DM + ANP, DM + BNP, and DM + CNP groups, respectively. The dose of ANP, BNP, and CNP was chosen by referring to previous studies (27,(54)(55)(56)(57)(58). After 28 days of infusion, these mice were euthanized for morphological and pathological detection.…”
Section: Animal Protocolsmentioning
confidence: 99%
“…It has been previously demonstrated that exercise-induced cardiac stress resistance is at least in part mediated through mitochondrial adaptation [ 39 , 40 , 41 ]. Musclin has been shown to govern exercise-induced mitochondrial biogenesis in skeletal muscles [ 22 ].…”
Section: Resultsmentioning
confidence: 99%